The width of life is more important than the length of life - Yakut, İdris; Kara, Meryem; Könte, Hasan Can; Özcan Çetin, Elif Hande; Korkmaz, Ahmet; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Topaloğlu, Serkan; Aras, Dursun (Kare Publishing, 2023)
[Abstract Not Available]
Keywords: Cardiology; Width of Life; Myocardial Infarction